2017
DOI: 10.12968/joan.2017.6.9.472
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder and addiction to medical aesthetic procedures

Abstract: According to the Diagnostic and Statistical Manual of Mental Disorders, body dysmorphic disorder (BDD), or dysmorphophobia, is the preoccupation with an imagined defect in appearance that leads to significant distress and impairments to daily functioning. Due to their lack of insight, individuals with BDD believe that cosmetic procedures will be the solution to their insecurities, even though they rarely get satisfaction from them. Cosmetic procedures can then become an addiction, as patients never reach full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The second situation, on the other hand, should serve as a warning to the professional to balance the risks and benefits of the procedure, since the patient may have body dysmorphia disorder or more generalized symptoms, such as anxiety. In such cases, patients may even experience a momentary satisfaction with the esthetic procedure; however, this may not be enough to bring them long-term benefits and satisfaction [5,55]. Thus, the professional should have the ability to suspect and identify possible patients with these conditions and to refer them to specialized professionals, such as psychologists and psychiatrists, for diagnosis and the elaboration of an adequate follow-up and/or treatment plan.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The second situation, on the other hand, should serve as a warning to the professional to balance the risks and benefits of the procedure, since the patient may have body dysmorphia disorder or more generalized symptoms, such as anxiety. In such cases, patients may even experience a momentary satisfaction with the esthetic procedure; however, this may not be enough to bring them long-term benefits and satisfaction [5,55]. Thus, the professional should have the ability to suspect and identify possible patients with these conditions and to refer them to specialized professionals, such as psychologists and psychiatrists, for diagnosis and the elaboration of an adequate follow-up and/or treatment plan.…”
Section: Plos Onementioning
confidence: 99%
“…Thus, we expect that the results of this study could help health care professionals to develop and improve a holistic view of human subjects, which would assist the development of patientcentered treatment plans. It is suggested that a detailed anamnesis be performed, including psychometric scales (such as those used in the present study) and a question about how many aesthetic treatments the patient has had previously [5]. In this regard, it is also important that curricula for training courses and continuing education programs are steadily enhanced, updating current social issues and new scientific evidence and methodology located at the frontier of different fields of knowledge.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the results also suggest that the demand for aesthetic dental treatment is not always solely motivated by a desire to improve a single physical aspect, pointing to the potential risks that treatments carried out indiscriminately and without individualized planning may have. This is because, in some cases, the demand for aesthetic dental treatment may be associated with psychological symptoms or disorders (e.g., dysmorphic disorder) [ 56 ] or social pressures as discussed above. For these, performing the aesthetic treatment may not have a long-term benefit [ 1 , 56 ] and may also contribute to worsening psychological symptoms or disorders and to the maintenance of social pressures and inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…This is because, in some cases, the demand for aesthetic dental treatment may be associated with psychological symptoms or disorders (e.g., dysmorphic disorder) [ 56 ] or social pressures as discussed above. For these, performing the aesthetic treatment may not have a long-term benefit [ 1 , 56 ] and may also contribute to worsening psychological symptoms or disorders and to the maintenance of social pressures and inequalities. As a result, no benefit, or even a negative impact on the patient’s well-being, may be observed.…”
Section: Discussionmentioning
confidence: 99%